Developing an evidence-based policy and protocol for human elephant conflict in oil palm plantations : (a case study of Sime Darby Plantation Berhad) - Ab. Ghani, Nur Aida (2020)
Palm oil is arguably one of the most controversial and scrutinised crops by European countries mainly due to their trading resolutions (Palm, 2016). Palm oil has become one of Malaysia’s major exports and provides substantial economic support to the livelihood in the country. However, with increased palm oil in rural areas comes increased chances for human-wildlife conflicts. As a result, there have been efforts to increase sustainability of the palm oil industry, which has developed guidelines to help in the management of human-wildlife conflict. The human-elephant conflict (HEC) in oil palm plantations commonly involves oil palm depredation by the elephants as well as reports of property damaged, and in some cases, loss of life for humans and elephants. This research is carried out with the aim to support co-existence between the agricultural society and elephants. Four objectives are determined which are: 1) to systematically review the literature of HEC and mitigation strategies used by palm oil plantations, particularly in Malaysia, 2) to describe HEC in Sime Darby Plantation Berhad operations, including details on the type of conflict and their patterns, 3) to evaluate the effectiveness of the current HEC mitigation measures practiced by Sime Darby Plantation Berhad and 4) to develop a HEC policy and Standard Operating Procedures (SOP) or protocol suitable for management and mitigation in oil palm plantations. The study sites for this research are within Sime Darby Plantation Berhad (SDPB) estates in Malaysia, mainly in Pahang, Johor and Sabah. This study synthesised 102 papers of past mitigation strategies used in the industry, obtained through Google Scholar, Scopus and Web of Science. These papers were reviewed and summarised under systematic themes using Excel. The information on HEC in SDPB Malaysia was acquired from voluntarily reports and past records in the estates. These data include the number of oil palm trees damaged by elephants, age of affected oil palm trees, frequency of HEC occurrence at daily, monthly or annual scale, and location of damage with covariates of mitigation measures such as electrical fencing and crop-guarding. Additionally, a rapid survey was conducted using Google Form for all estates under SDPB Malaysia operations, excluding Sarawak, to assess information of elephant sightings and mitigation used. This research found that 38% (N=102) papers discussed the use of electric fences as mitigation and 9% used crop-guarding. Other methods include carbide, “bomoh” (supernatural belief), patrolling, elephant-proof trenching, improved design fencing, translocation, culling, elephant drive, conservation research and conservation awareness. Overall, 55.15% (N=200,242) of the damaged trees were a year old and the likelihood of trees being damaged reduced significantly after the fifth year. It is common for agriculture plantations, when experiencing Human-Elephant Conflict (HEC), to use physical barriers to prevent wild elephants from entering the plantation areas. The finding that 97% of damages occurred to trees aged 5 years and below indicates that plantations can co-exist with elephants in areas with trees aged 6 years and above, and this can be further explored by future research. The highest intensity of damage was 14,002 trees which occurred in the P2011A field of the estate in Pahang. Between the year 2011 and 2018, the highest frequencies of HEC recorded were 94 times at forest borders of Pahang Estate followed by 90 times at the fields bordering the mangrove forest of Sandakan. The monthly analysis of HEC damage showed irregular patterns for all plantations. The total loss linked to HEC for the eight estates between 2011 and 2018, was RM 24,227,234.70. Logistic regression test demonstrated that some but not all estates which installed electric fencing managed to reduce the number of trees damaged. The company’s Saving the Orang Utan Policy which focuses on endangered and protected species, states the commitment to manage human-wildlife conflict responsibly, which is to be improved on and supported by action on the ground. This study records the protocol for managing HEC at SDPB estates for the first time, recommends a potential tool and platform that can be duplicated at other plantations to systematically record and manage their HEC, and has standardised the format to calculate and report financial loss of elephant depredation in the industry. The research achieves its aim by providing data on how plantations can co-exist with wild elephants. However, the data also reveals that this type of coexistence may be applicable to particular conflict areas only, as some plantations had experienced damages to older trees.